Impact of Covid- 19 Pandemic Lockdown on Social-Economic Development in Rivers State. - Doreen, Kobani; Lolo Sax Fubara, Hailsham, (International Journal of Scientific Research and Management (IJSRM), 2022)
This study examined the Impact of COVD-19 Pandemic Lockdown on Social-economic Development in Rivers State. Descriptive survey research design was adopted for the study. The population for the study comprises 1,479 leaders and 9,783 members of registered Community Based Organizations (CBOs) in the three senatorial districts of Rivers State making a total of 11,262. The proportionate sampling technique was used to select the sample size of 1,496 respondents made up of 437 leaders and 1,059 members. The instrument used for data collection was a structured questionnaire titled: Impact of COVID-19 Pandemic Lockdown on Social-Economic Development Assessment Questionnaire (ICPLSEQAQ). The reliability of the instrument was determined through a pilot study, while Cronbach Alpha Statistic Method was used to establish the reliability coefficient (r) value of 0.78. Four research questions were posed to guide the study. The research questions were analysed with mean and standard deviation statistic.The findings from the study revealed that COVID-19 pandemic lockdown control measures had negative impact on the educational development, health care services, agricultural productivity, and supply of goods/services for small scale businesses in Rivers State. Based on the findings, the study recommended amongst others that government at all levels should prioritise education by providing ICT gadgets as alternative ways of learning and training students and teachers on how to use it for learning to avoid being left behind in terms emergency situations like that of COVID-19 Pandemic.